About Some Actual Problems of the Methodology of Research of State Legal Phenomena - Vladimir Valentinovich Kozhevnikov (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
This scientific article is devoted to the consideration of some methodological problems of the study of state and legal phenomena. The main purpose of the work is to draw the attention of the scientific community to those general theoretical methodological issues that are ambiguously solved by scientists and which are important for legal science. To achieve this goal during the study, the following tasks were solved: 1) substantiate the importance and necessity of the general philosophical method; 2) to argue the unacceptability of the religious and moral approach to the study of state and legal reality; 3) dialectically assess such a methodological principle as the principle of scientific pluralism. In conclusion, it is concluded that, firstly, that general philosophical methods, in particular and especially the method of dialectical and historical materialism, which form the methodological basis for the scientific study of state-legal phenomena, should not be ignored, because they reveal the most general laws of the movement of human thought to the truth, concentrating all the most important and essential that is contained in other methods; secondly, the religious philosophy of believers should not be included in the potential of the methodology of cognition of state and legal reality; thirdly, the methodological principle of scientific pluralism must have appropriate boundaries.